Theorems on Compatible Mapping Types in Complete Menger Space - Chaudhary, Ajay Kumar (The Nepali Mathematical Sciences Report, 2024)
This research article presents two common fixed theorems in complete Menger space in two pairs of self-mappings by using altering distance function in the context of compatible mappings of type (P) and compatible mappings of type (K). Article discusses the topological properties of Menger spaces and mappings between these spaces. This result generalizes the result of Khan et al.[18], and extends the results of [8], and [9].